The Impact of Social Capital on Vietnam Rural Economic Development - Anh, Tran Phuong (Business and Economic Research, 2024)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Social capital is always considered as an important resource in the development process. In each nation, social capital shows different characteristics; as a result, these differences create varieties in both styles’ lives and social relationships. Usually, social capital is traditionally studied in the sociology field; however, this research will examine it from an economic perspective; and focus to discourse on social capital within the context of economic development in rural areas in Vietnam - a middle-income developing country. Through the author’s practical experiences in 6 rural areas in northern Vietnam, combined with in-depth interviews with farmers in these 6 regions and official statistical data from state agencies, the article has synthesized and summarized and pointed out the impact of social capital on Vietnam’s rural economic development.